Assessment and Diagnosis of Musculoskeletal Shoulder Disorders over the Internet - Leah Steele; Hannah Lade; Stephanie McKenzie; Trevor G. Russell (International Journal of Telemedicine and Applications)
Shoulder disorders are common, debilitating, and represent a considerable burden on society. As primary contact practitioners, physiotherapists play a large role in the management and rehabilitation of people with these conditions. For those living outside of urban areas, however, access to physiotherapy can be limited. The aim of this study was to evaluate the validity and reliability of using a telerehabilitation system to collect physical examination findings and correctly identify disorders of the shoulder. Twenty-two participants with 28 shoulder disorders were recruited and underwent a face-to-face physical examination and a remote telerehabilitation examination. Examination findings and diagnoses from the two modes of assessment were used to determine validity and reliability of the new method. Diagnostic agreement and agreement on individual findings between the two methods were found to be consistent with the reliability of conventional assessment methods. This study provides important preliminary findings on the validity and reliability of musculoskeletal examinations conducted via telerehabilitation.